2020
DOI: 10.1017/s0263574720000648
|View full text |Cite
|
Sign up to set email alerts
|

A Human Arm’s Mechanical Impedance Tuning Method for Improving the Stability of Haptic Rendering

Abstract: SUMMARY Rendering of rigid objects with high stiffness while guaranteeing system stability remains a major and challenging issue in haptics. Being a part of the haptic system, the behavior of human operators, represented as the mechanical impedance of arm, has an inevitable influence on system performance. This paper first verified that the human arm impedance can unconsciously be modified through imposing background forces and resist unstable motions arising from external disturbance forces. Then, a reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The largest eigenvector obtained from this characteristic formula is the optimal PCA transform vector [12]. In the PCA dimensionality reduction process, it is usually necessary to manually adjust the reduced size [13]. The transformation matrix after dimensionality reduction can be…”
Section: Pattern Recognition Methodsmentioning
confidence: 99%
“…The largest eigenvector obtained from this characteristic formula is the optimal PCA transform vector [12]. In the PCA dimensionality reduction process, it is usually necessary to manually adjust the reduced size [13]. The transformation matrix after dimensionality reduction can be…”
Section: Pattern Recognition Methodsmentioning
confidence: 99%
“…Substituting equation (12) into equation (11) and then taking equation (11) into equation 10, we obtain S R . To learn this model, we assume that the Gaussian noise affects the measurement of the stiffness matrix S iden (i).…”
Section: B Arm Impedance Parameter Identification and Stiffness Contmentioning
confidence: 99%
“…Many researchers have performed static and dynamic analyses of the impedance parameters of the human arm [4]- [8]. The arm endpoint stiffness, as the most important impedance gain (among mass, damping, and stiffness) [9], greatly influences operation tasks [10], [11] in the form of an endpoint stiffness ellipsoid [12]. Many studies have revealed that the arm endpoint stiffness is mainly affected by arm configurations [13], [14] and the co-contraction effect of antagonistic muscles [15].…”
Section: Introductionmentioning
confidence: 99%